Pengembangan Modul Kerja Praktik dan Disposisi Berbasis Web pada PT Pertamina Geothermal Energy - Vina Septia Anggraeni; Yopi Nugraha (LPPM STT Terpadu Nurul Fikri, 2026)
The management processes for internship activities and document disposition at PT Pertamina Geothermal Energy (PGE) are still carried out manually, leading to inefficiencies in document validation and tracking. This study focuses on the development of SIGAP PGE, a web-based information system that integrates internship modules and document disposition features to support the digitalization of internal administrative workflows. The system was developed using the Waterfall method, which includes the stages of requirements analysis, system design, implementation, testing, and maintenance. The system was built using the CodeIgniter 4 framework, a MySQL database normalized up to the Third Normal Form (3NF), and employs Role-based access control to ensure data security. Based on Black Box Testing, all system functionalities operated as specified. Additionally, the ID Card validation process demonstrated a 62% improvement in efficiency compared to the previous manual procedure. Key features of the system include internship participant data management, four-level hierarchical validation, automated notifications, and real-time digital document disposition. The implementation of SIGAP PGE has enhanced efficiency, transparency, and administrative accountability within PGE. Therefore, this study concludes that a web-based integrated system significantly accelerates document validation and disposition processes in a structured corporate environment, while offering further development potential through RESTful API integration.